Paramedics and pre‐hospital management of acute myocardial infarction: diagnosis and reperfusion - Johnston, S (BMJ Group, 2006)
In this paper, we discuss and critically analyse pre‐hospital management of acute myocardial infarction (AMI). It is clear from several large studies that rapid diagnosis and application of thrombolysis reduces morbidity and mortality rates. Strategies that improve time to treatment in the pre‐hospital setting are therefore of fundamental importance in the management of this fatal disease. The advantage of 12 lead electrocardiography use by paramedics to diagnose AMI and reduce time to treatment is discussed. Moreover, paramedic application of thrombolysis in the pre‐hospital environment is examined. Several studies conducted worldwide support the notion that ambulance services can play a role in minimising time to treatment for patients with AMI. The contribution of early intervention by paramedics trained in critical care is potentially considerable, particularly in the important chain of survival that is often initiated by pre‐hospital intervention.